Uji Aktivitas ALT, AST dan Histopatologi Ekstrak Etanol Rimpang Temu Kunci (Boesenbergia rotunda (L.) Mansf) pada Tikus Putih Jantan - Mawandha Sari Harahap; Urip Harahap; Panal Sitorus (Journal of Pharmaceutical and Health Research, 2023)
Experimental research in the field of hepatology on the development of traditional medicine into a potential pharmacological solution to protect the liver from cirrhosis. Accordingly, this study investigated the effect of ethanol extract of temu kunci rhizome on liver cirrhosis. The rats were divided into six groups, the normal control group was given nothing but pellets and sufficient water, the negative control group was given orally CMC-Na 0.5%, 200 mg acetylcysteine (dose converted to rat) was given to the positive control group, and the treatment group was given ethanol extract of temu kunci rhizome doses of 250, 500, 750 mg/kg BW, given daily for 10 days. Then on the 10th day after 1 hour of extract administration, induction was carried out with paracetamol 800 mg/kg BW orally; 16 hours after induction, rats were sacrificed, blood was taken for ALT and AST enzyme examination, then liver organs were taken for histopathological examination. The administration of ethanol extract of temu kunci rhizome can prevent liver damage by reducing ALT and AST enzyme levels in rat blood serum. The best dose in reducing ALT and AST enzymes was produced by giving 500 mg/kg BW of temu kunci rhizome ethanol extract every day for 10 days. At a dose of 500 mg/kg BW ethanol extract of temu kunci rhizome morphologically (evaluation with H&E staining) can also repair liver tissue damaged by paracetamol induction. The development of liver damage can be interpended by using ethanol extract of temu kunci rhizome, so that the status of liver morphology, structure and function of the liver can be maintained.